1982
DOI: 10.1068/p110057
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Pictograms, Pictures, and Words Separately and All Mixed up

Abstract: Pictograms were created in which the outline of a work denoting an object was shaped to be the same as the object itself. A number of objects were presented, some drawn as pictograms, some as outline shapes, and some as normally printed words. The experiment was designed to test if recognition memory was superior for the pictograms as compared to outline pictures or words, and if this would be true whether the subjects were asked to attend to the form or only the content of the stimuli. One group of subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…visuo-spatial and phonological loops). In addition, it is generally found that usually people remember pictures better than they remember words (Haber and Myers 1982;Paivio 1990;Esgate and Groom 2005, p. 15).…”
Section: Psychological Backgroundmentioning
confidence: 99%
“…visuo-spatial and phonological loops). In addition, it is generally found that usually people remember pictures better than they remember words (Haber and Myers 1982;Paivio 1990;Esgate and Groom 2005, p. 15).…”
Section: Psychological Backgroundmentioning
confidence: 99%
“…This is called the "pictorial superiority effect." Memory for a picture-word combination is superior to memory for words alone or pictures alone (Haber & Myers, 1982).…”
Section: Picture Perceptionmentioning
confidence: 99%
“…It is also known that our memory for a picture-word combination is superior to our memory for words alone, or to our memory for pictures alone. [6] As to the printed material, the knowledge about Graphic Design of instructional material is relevant. Graphic Design is a tool by which we can manipulate the raw materials-words in different typefaces, sizes, styles, empty space, illustrations, colour, paper and ink, and the final number of pages-to achieve the best possible communication between people.…”
Section: Inner Contextmentioning
confidence: 99%